Employment Intensity of Economic Growth: Evidence from Nepal - Dahal, Madhav Prasad; Rai, Hemant (Economic Journal of Development Issues, 2019)
Economic growth and employment are taken as the top twin objectives of macroeconomic policy agenda in both developed and developing countries. Economic growth brings changes in employment growth. In general, during time of the growth of gross domestic product (GDP) increasing employment opportunities are created while unemployment will be rising during economic deceleration. This paper examines employment intensity of growth in (i) the economy of Nepal in totality, (ii) three broad economic sectors, and (iii) different sub-sectors of the economy over the period 1998-2018. Empirical result indicates labor-intensive growth in Nepal over the review period. There is no indication of jobless growth.